2020
DOI: 10.3389/fnagi.2020.00070
|View full text |Cite
|
Sign up to set email alerts
|

Novel Targets for Stroke Therapy: Special Focus on TRPC Channels and TRPC6

Abstract: Stroke remains a leading cause of death, disability, and medical care burden worldwide. However, transformation from laboratory findings toward effective pharmacological interventions for clinical stroke has been unsatisfactory. Novel evidence has been gained on the underlying mechanisms and therapeutic potential related to the transient receptor potential (TRP) channels in several disorders. The TRP superfamily consists of a diverse group of Ca 2+ permeable non-selective cation channels. In particular, the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 105 publications
(124 reference statements)
0
18
0
Order By: Relevance
“…Ca 2+ overload is one of the main molecular mechanisms involved in ischemic cell damage and death [56]. TRPC6, along with a few other prominent members of the family, has recently gained considerable attention as a promising target for the prevention of Ca 2+ overload [23]. Dysregulation of TRPC6 activity has been implicated in ischemic stroke [23,57], as well as retinal ischemia [58], and renal hypoxia following cerebral ischemia [59].…”
Section: Role Of Trpc6 In the Development Of Ischemiamentioning
confidence: 99%
See 4 more Smart Citations
“…Ca 2+ overload is one of the main molecular mechanisms involved in ischemic cell damage and death [56]. TRPC6, along with a few other prominent members of the family, has recently gained considerable attention as a promising target for the prevention of Ca 2+ overload [23]. Dysregulation of TRPC6 activity has been implicated in ischemic stroke [23,57], as well as retinal ischemia [58], and renal hypoxia following cerebral ischemia [59].…”
Section: Role Of Trpc6 In the Development Of Ischemiamentioning
confidence: 99%
“…Recent studies have shown that TRPC6-mediated signaling promotes neuronal survival [60], the brain-derived neurotrophic factor-mediated axonal growth cone guidance [61], dendritic outgrowth and branching [17], and excitatory synapse formation [13]. In addition, positive modulation of TRPC6 activity allows for the sustained activation of the CREB/CaMK-IV and Ras/MEK/ERK pathways, which is vital for neuronal development, survival, and proper functioning [23]. Blocking CREB signaling hinders post-stroke recovery [62], and CaMK-IV inhibition impairs blood-brain barrier integrity and exacerbates ischemic injury [63].…”
Section: Role Of Trpc6 In the Development Of Ischemiamentioning
confidence: 99%
See 3 more Smart Citations